Psychometric properties of a short form of the Inventory of - Besharat, Mohamad ali; Mohammad Mehr, REza; Pourbohlool, Samaneh; Azizi, Leila (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim Interpersonal problems are difficulties that an individual experiences in relating to others and are sources of subjective distress. The main purpose of this study was to examine reliability, validity, and exploratory factor analysis of a short form of the Inventory of Interpersonal Problems in an Iranian students. Materials and methods This is a psychometric study and analysis of the data involved mainly descriptive statistics. 647 volunteers (490 females, 434 males) from universities in Tehran were included in this study. All participants were asked to complete the Inventory of Interpersonal Problems (IIP-60), the Mental Health Inventory (MHI-28), the Self-Esteem Rating Scale (SERS), and the Emotional Intelligence Scale (EIS). The scale was validated with construct, convergent and discriminant validity. Its reliability was measured by internal consistency and test-retest reliability methods. Findings The results of explarotary factor analysis supported six factors for the IIP-60 as well as a single general factor of interpersonal problems. The convergent and discriminant validity of the IIP-60 were supported by an expected pattern of correlations between the scale and the measures of mental health, self-esteem, and emotional intelligence. Coefficient alpha estimates of internal reliability were between .82 and .93 for the IIP-60 subscales. Test-retest reliability of the IIP-60 was also calculated at the range of .65-.81. All correlations were statistically significant. Conclusion It can be concluded that the Inventory of Interpersonal Problems (IIP-60) is a valid and reliable scale to measure interpersonal problems. Keywords: Inventory of Interpersonal Problems (IIP-60), Reliability, Validity, Exploratory factor REFERENCES -Alden LE Wiggins JS Pincus AL (1990) Construction of circumplex scales for the Inventory of Interpersonal Problems. Journal of Personality Assessment. 55(3-4) 521-536. -Austin EJ et al (2004). Measurement of trait emotional intelligence: Testing and cross-validating a modified version of Schutte et al.’s (1998) measure. Personality and Individual Differences. 36 (3) 555-562. -Barkham M Hardy GE Startup M (1996). The IIP-32: A short version of the Inventory of Interpersonal Problems. British Journal of Clinical Psychology. 35 (1) 21-36. - Besharat MA (2006a). [Psychometric properties of the Inventory of Interpersonal Problems (IIP-127)]. Research Report: University of Tehran, Tehran. (Persian) - Besharat MA (2006b). [Reliability and Validity of the Mental Health Inventory]. Faslnameh Daneshvar Raftar. 16 (6) 11-16. (Persian). - Besharat MA (2007a). [Psychometric properties of the Self-Esteem Rating Scale]. Research Report: University of Tehran, Tehran. (Persian) - Besharat MA (2007b). Psychometric properties of Farsi version of the Emotional Intelligence Scale-41 (FEIS-41). Personality and Individual Differences. 43 (5) 991-1000. -Besharat MA (2008). [Reliability and validity of the Inventory of Interpersonal Problems (IIP-127)]. Daneshvar Raftar. 28(1) 13-20. (Persian) -Besharat MA (2009). [Reliability and validity of a short form of the Mental Health Inventory in an Iranian population]. Forensic Medicine. 15(2) 87-91. (Persian) -Cattell RB (1966). The scree test for the number of factors. Multivariate Behavioral Research. 1(2) 245-276. - DiTommaso E et al (2003). Attachment styles, social skills and loneliness in young adults. Personality and Individual Differences. 35(2) 303–312. -Goldberg DP Williams PA (1988). A Users' Guide to the General Health Questionnaire. Berkshire: NFER, Nelson. -Gude T et al (2000). Inventory of Interpersonal Problems: A three-dimensional balanced and scalable 48-item version. Journal of Personality Assessment. 74(2) 296-310. -Gurtman MB (1992). Trust, distrust, and interpersonal problems: A circumplex analysis. Journal of Personality and Social Psychology. 62(6) 989-1002. -Gurtman MB (1995). Personality structure and interpersonal problems: A theoretical-guided item analysis of the Inventory of Interpersonal Problems. Personality Assessment. 2 (4) 343-361. -Gurtman MB (1996). Interpersonal problems and the psychotherapy context: the construct validity of the Inventory of Interpersonal Problems. Psychological Assessment. 8(3) 241-255. -Hoffart A (1997). Interpersonal problems among patients suffering from panic disorder with agoraphobia before and after treatment. British Journal of Medical Psychology. 70(2) 149-157. -Horowitz LM (1979). On the cognitive structure of interpersonal problems treated in psychotherapy. Journal of Counsulting and Clinical Psychology. 47 (1) 5-15. -Horowitz LM et al (1982). The Prototype of a Lonely Person. In LA Peplau Perlman D (Eds) Loneliness: A Sourcebook of Current Theory, Research and Therapy. New York: Wiley Interscience. -Horowitz LM et al (1988). Inventory of interpersonal problems: psychometric properties and clinical applications. Journal of Counsulting and Clinical Psychology. 56 (6) 885-892. -Horowitz LM, Vitkus J (1986). The interpersonal basis of psychiatric symptoms. Clinical Psychology Review. 6 (5) 443-469. - Hudson W (1982). The Clinical Measurement Package: A Field Manual. Homewood, IL: Dorsey Press. - Lam D et al (2003). Response style, interpersonal difficulties and social functioning in major depressive disorder. Journal of Affective Disorders. 75(3) 279–283. -Markowitz JC et al (1996). Interpersonal improvement in chronically depressed patients treated with desipramine. Journal of Affective Disorders. 41(1) 59-62. -Mayer JD Salovey P (1997). What is emotional intelligence? In Salovey P and Mayer JD (Eds.). Emotional development and emotional intelligence (pp. 3-31). New York: Basic Books. -Nugent WR, Thomas J (1993). Validation of the Self-Esteem Rating Scale. Research on Social Work Practice. 3(2) 191-207. -Saklofske DH et al (2003). Factor structure and validity of a trait emotional intelligence measure. Personality and Individual Differences. 34(4) 707-721. -Salovey P, Mayer JD (1990). Emotional intelligence. Imagination, Cognition and Personality. 9(3) 185-211. -Savournin R et al (1995). The elusive factor structure of the Inventory of Interpersonal Problems. British Journal of Medical Psychology. 68 (4) 353-369. -Schutte NS et al (1998). Development and validation of a measure of emotional intelligence. Personality and Individual Differences. 25 (2) 167-177. - Segrin C Taylor M (2007). Positive interpersonal relationships mediate the association between social skills and psychological well-being. Personality and Individual Differences. 43 (4) 637–646. -Soldz S et al (1995). A short form of the Inventory of Interpersonal Problems Circumplex Scales. Psychological Assessment. 2, 53-63. -Tse WS Yip THJ (2009). Relationship among dispositional forgiveness of others, interpersonal adjustment and psychological well-being: implication for interpersonal theory of depression. Personality and Individual Differences. 46(3) 365–368. -Veit CT Ware JE (1983). The structure of psychological distress and well-being in general population. Journal of Consulting and Clinical Psychology. 51(5) 730-742. -Wenzel A et al (2005). Communication and social skills in socially anxious and nonanxious individuals in the context of romantic relationships. Behaviour Research and Therapy. 43 (4) 505–519. - Worthington EL et al (2007). Forgiveness, health, and well-being: a review of evidence for emotional versus decisional forgiveness, dispositional forgivingness, and reduced unforgiveness. Journal of Behavioral Medicine. 30 (4) 291–302.